EFEKTIVITAS PENAMBAHAN CHITOSAN DALAM PENGAWETAN IKAN GABUS (Ophiocephalus striatus) ASIN SEBAGAI RANCANGAN LEMBAR KERJA SISWA (LKS) PADA PEMBELAJARAN IPA DI SMP - Gusti Robi Wala; Darmawati '; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research was to determine the effectiveness of added chitosan on preservation of salted common snakehead (Ophiocephalus striatus) as student worksheet design on science learning in Junior High School. This research was conducted on March until May 2016. The research used using completely randomized design (CRD) non factorial, which consists of 4 treatments and 3 replicates. The parameters observed were water content, protein content, fat content, and hedonic quality test: appearance, aroma, flavor and texture. The result showed that added chitosan was significant effect on water content, protein content and fat content of salted common snakehead. The best treatment was chitosan concentration of 2% where decrease the water content 16.496%, 1.850% fat content and also increase the protein content 43.105%. While on the hedonic duality test showed the appearance of salted common snakehead most preferred panelist in the treatment is 1%, the aroma and flavor is 2%, also the texture is 3%. The result of this research was used as student worksheet design on science learning in Junior High School.Key words: Chitosan, Salted Common Snakehead, Student Worksheet Design